The Protective Role of Alkaline Ionized Water Against Dental Erosion from Acidic Beverages: An In-Vitro Analysis - Krithika D, Shubhashini N, Annapoorna Kini, Vinay Chandra R, Venkata Suresh Venkataiah, Mohmed Isaqali Karobari, Syed Nahid Basheer, Syed Wali Peeran, Savadamoorthi Kamatchi Subramani, Mohammed Zameer (South Eastern European Journal of Public Health, 2025)
Objectives:The prevalence of dental erosion has increased due to the regular intake of energy drinks and sports beverages, necessitating the implementation of effective preventive measures. Therefore, this study aimed to evaluate protective role of Alkaline Ionized Water (AIW) against dental erosion induced by energy drinks and sports beverages by assessing enamel microhardness as a quantitative measure of demineralization. Material and Methods:Sixty healthy mandibular molars were prepared by removing their crowns and divided them into buccal and lingual halves. The buccal sections were polished, affixed to acrylic blocks, and then allocated into six categories: GROUP 1 (distilled water - negative control), GROUP 2 (a popular carbonated beverage - positive control), GROUP 3 (energy drink), GROUP 4 (sports beverage), GROUP 5 (energy drink + AIW), and GROUP 6 (sports beverage + AIW). The samples were exposed to their respective solutions for 10 minutes daily over three days. Changes in Enamel microhardness was investigated by Knoop microhardness test were performed before and after the exposure period. Statistical analysis included one-way ANOVA and Tukey’s Posthoc test.Results: Significant differences in enamel microhardness were observed between groups. AIW-treated groups (Groups 5 and 6) showed higher microhardness compared to those exposed only to acidic beverages. Group 6 demonstrated the best protective outcome, followed closely by Group 5. Groups exposed to acidic drinks without AIW intervention (Groups 2–4) demonstrated significant reductions in microhardness, with Group 2 (carbonated beverage) displaying the most pronounced erosion.Conclusion:AIW demonstrated efficacy in neutralizing the erosive effects of acidic beverages on enamel, offers a potential preventive measure against beverage induced dental erosion. Further long-term studies are required to explore AIW’s long term effects and broader applications in oral health management.